Panentheism and cosmopolitanism: a short introduction to the philosophy of Karl Christian Friedrich Krause (1781-1832) - Göcke, Benedikt Paul (Peter Lang, 2024)
"Karl Christian Friedrich Krause (1781-1832) develops a fascinating cosmopolitanism against the background of his panentheistic metaphysics. In Krause's panentheistic cosmopolitanism, every individual, every family, every friendship, every nation, every league of peoples, and finally, the global civil society itself is called upon to realize the ideals of virtue, law, beauty, and divinity. Because in Krause's panentheistic system of philosophy, humanity is at the centre of the Absolute, as the union of Reason and Nature, humanity is, in effect, called upon, and is capable of establishing the league of humanity as the image of the Absolute, in and by freedom for excellence"--